Partisipasi dalam Pengambilan Keputusan pada Pemerintahan Nabi Muhammad SAW. di Madinah - Suryanto, Sasmika Dwi (POLITEA, 2022)
The title of this research is the alignment of democracy with Islamic governance practices, especially in terms of participation in decision-making. The purpose of this study is to describe how aspirations are accommodated in the government of the Prophet Muhammad SAW. The purpose of more detail in this study is to see further whether decision-making in the government of the Prophet was in line with democratic principles. This research was conducted using the literature study method using qualitative analysis. The focus of this article is related to the space for conveying aspirations in the practice of decision making in the government of the Prophet Muhammad in Medina. The conclusion obtained from the results of the discussion is that the government of the Prophet Muhammad SAW is capable of aspirations in decision making through the opportunity to express opinions. Democratic values are also present in the process of delivering this opinion. Freedom of opinion is for things that are not determined by revelation. Participatory decision making is done through mushararah (syuro), consultative and initiative.